Chemical diversity, medicinal potentialities, biosynthesis, and pharmacokinetics of anthraquinones and their congeners derived from marine fungi: a comprehensive update. Issue 38 (1st September 2022) - Sebak, Mohamed; Molham, Fatma; Greco, Claudio; Tammam, Mohamed A.; Sobeh, Mansour; El-Demerdash, Amr
Abstract : Marine-derived fungi receive excessive attention as prolific producers of structurally unique secondary metabolites. Whilst they are promising substitutes or conjugates for current therapeutics, so far research has only touched on their secondary metabolite diversity. Abstract : Marine fungi receive excessive attention as prolific producers of structurally unique secondary metabolites, offering promising potential as substitutes or conjugates for current therapeutics, whereas existing research has only scratched the surface in terms of secondary metabolite diversity and potential industrial applications as only a small share of bioactive natural products have been identified from marine-derived fungi thus far. Anthraquinones derived from filamentous fungi are a distinct large group of polyketides containing compounds which feature a common 9, 10-dioxoanthracene core, while their derivatives are generated through enzymatic reactions such as methylation, oxidation, or dimerization to produce a large variety of anthraquinone derivatives. A considerable number of reported anthraquinones and their derivatives have shown significant biological activities as well as highly economical, commercial, and biomedical potentialities such as anticancer, antimicrobial, antioxidant, and anti-inflammatory activities. Accordingly, and in this context, this review comprehensively covers the state-of-art over 20 years of about 208 structurally diverse anthraquinones and their derivatives isolated from different species of marine-derived fungal genera along with their reported bioactivity wherever applicable. Also, in this manuscript, we will present in brief recent insights centred on their experimentally proved biosynthetic routes. Moreover, all reported compounds were extensively investigated for their in-silico drug-likeness and pharmacokinetics properties which intriguingly highlighted a list of 20 anthraquinone-containing compounds that could be considered as potential drug lead scaffolds.